Development of an E-Catalog of Dutch Colonial Relics in the Bekri Region of Central Lampung as a Local History Learning Resource - Yudi Hartono; Nurfayatun Khasanah; Johan Setiawan (AL-ISHLAH: Jurnal Pendidikan, 2025)
This research addresses the need for localized history learning resources by developing an E-catalog of Dutch Colonial Heritage in the Bekri area of Central Lampung for use in SMAN 2 Metro. The objectives are: (1) to analyze students' learning needs, (2) to design an E-catalog as a local history learning source, and (3) to assess expert and practitioner feedback on the E-catalog design. The study employs the Research and Development (RD) method. Data collection techniques include observation, interviews, questionnaires, and documentation. The validation process involves both media and material experts, followed by small group testing. The developed E-catalog showcases various Dutch colonial buildings from 1916 to 2024 in Bekri. Validation results indicate high feasibility. Material expert validation yielded an 80% score, categorized as "very good," while media expert validation scored 91%, also categorized as "very good." In small group testing involving ten students, five students rated the E-catalog as "very suitable" (100%), one student gave a "very suitable" score of 90%, one student rated it 85% ("very decent"), two students rated it 80% ("decent"), and one student rated it 60% ("quite decent"). The findings suggest that the E-catalog is a valid and effective local history learning resource. However, further large-scale testing is recommended to generalize the results. Future research may explore integrating interactive elements to enhance student engagement.